Ensino de Libras e polarização docente: um estudo sobre os posicionamentos dos professores na perspectiva da análise crítica do discurso - Santana, Neemias Gomes (2024)
This research is linked to the historical, social, and political context of the Deaf Community, as the linguistic identity of the individual is constituted from the social identity (Quadros; Karnopp, 2004). From this perspective, this research is related to the field of Linguistics through the postulates of Critical Discourse Analysis (CDA), mainly due to its commitment to vulnerable groups, and aims to analyze the polarized positions of the voices present in the discourses of Libras teachers (Deaf and nondeaf) who work as Libras teachers in public and/or private educational institutions. The work will highlight the voices of Deaf teachers who defend the visibility and protagonism of Deaf people, as well as the right to education and the teaching of Libras as one of the cultural artifacts of this community. In accordance with the transdisciplinary nature of Critical Discourse Analysis (Fairclough, 2012), we dialogue with Deaf Studies (Stumpf, 2005; Petit, 2008; Silva, 2008; Strobel, 2008; Gesser, 2012; Perlin, 2016). The corpus of this study is formed from comments by Libras teachers on the theme “Teaching of Libras by hearing people”, extracted from the social network Instagram. We examine the corpus based on the qualitative-interpretative methodological approach (Magalhães; Martins; Resende, 2017; Nunes, 2021), following the methodological procedure suggested in ASCD (Pedrosa, 2016, 2018; Cunha, 2021). For a Textually Oriented Analysis, we use Systemic-Functional Grammar (Fuzer; Cabral, 2014), which focuses on the perspective of the social context of language use. Among the systems studied by this Grammar, we chose the category Evaluativity, proposed by Martin (2004), Martin and White (2005) and Martin and Rose (2003, 2007), focusing specifically on the Engagement subsystem, which allows understanding the presence of monoglossia and heteroglossia in these discourses. Based on the results of the analyses, we aim to find evidence, arguments and/or data regarding the teaching of Libras in Brazil, and the understanding of the historicaldiscursive process of intercultural and bilingual education for Deaf people in the country. In this way, we seek to highlight the importance of an approach that contributes to the construction of a praxis that promotes reflective dialogues between Deaf and non-Deaf people, recognizing the need for this thinking for the promotion of inclusion and effective communication between these groups in social, political, identity and cultural interactions.